INTERCULTURAL COMMUNICATION AND ITS ROLE IN LINGUISTICS - Ibrokhimova Mokhinur Mukhammadkurbanovna (International Journal of Literature and Language Studies, 2026)
This article provides a comprehensive analysis of intercultural communication and its significant role within the field of linguistics. It examines how linguistic practices, cultural norms, and pragmatic competence influence effective cross-cultural interactions. The study emphasizes the importance of understanding cultural context, language variations, and nonverbal communication cues in fostering successful communication between speakers from diverse cultural backgrounds. By exploring both theoretical frameworks and practical applications, the article highlights strategies to enhance intercultural competence, improve language learning outcomes, and reduce misunderstandings in multicultural environments.